Development of an Encyclopedia Book for Anatomy and Morphology of Plants on the Morphological Identification of Orchid Plants (Orchidaceae) in Kampoeng Anggrek Kediri - Rizky Intan Adina Putri; Haslinda Yasti Agustin (Bioeduca : Journal of Biology Education, 2023)
The low level of understanding of biology students on plant morphology material, especially Orchidaceae, requires the development of learning resources. This study aims to develop an encyclopedia "Identification of Orchidaceae Morphology" and test its feasibility. Research and development was carried out in 2 stages, namely identification of the morphology of Orchidaceae and development of an encyclopedia using the ADDIE model (analysis, design, development, implementation and evaluation). The results of the study, the eleven identified orchid plants had similarities in the flower parts included in the flower tent because they could not be distinguished between the petals and the corolla. An encyclopedia book containing taxonomy of orchid plants, scientific names, identification descriptions of orchid plants along with pictures. The results of the percentage score of material experts was 77.17%, media experts were 88%, and lecturers of Plant Anatomy and Morphology were 83.65%. The results of student implementation obtained an average percentage score of 85.34%. The developed encyclopedia has a decent quality to be used as a learning resource.